Designing a doctor evaluation index system for an online medical platform based on the information system success model in China - Liu, Shuaibing; Zhang, Yunqiu (Frontiers in Public Health, 2023)
Objective In the context of “internet + medical health” and emphasis on evaluation mechanism for medical and health talents in China, we design an evaluation index system for doctors on online medical platforms by synthesizing two patterns of existing online medical platforms, which is the first step to enhance the capabilities of doctors on online medical platforms. Methods Based on the doctor evaluation model integrating information systems success model (ISS-DE model) and grounded theory, the evaluation indicators were obtained through expert interviews, offline medical institutions investigation, online platforms investigation, and literature research, and were assigned weights using the analytic hierarchy process (AHP) method. A working group composed of 23 experts was set up to review and determine the competency standards of doctors on the online medical platforms. Results A new indicator framework covering 3 dimensions of system quality, service quality and information quality was constructed in this study. The index system included 3 first-level indicators, 8 s-level indicators and 60 third-level indicators, and each indicator was given different weightage. Conclusion The complete index system constructed by the Delphi method in this study is suitable for China’s online medical platforms, which will help to improve the quality of platforms and the ability of doctors, thus promoting the process of internet medical integration.